Key Strategies to Overcome Cost Overruns Issues in Building Maintenance Management - Gala Mong, Sylvia; Fikri Mohamed, Sarajul; Saidin Misnan, Mohd (International Journal of Engineering and Technology, 2018)
The building maintenance is a crucial part of the life cycle of the building. The maintenance strategies are planned to maintain the condition of the building for specified functions. The maintenance planning requires a comprehensive assessment in determining the effectiveness of building performance, especially in the maintenance budgets planning process. The effective budget preparation will reduce the risk of cost overruns and help the organization to execute the repair works efficiently with sufficient resources. This study attempts to identify the issues related to maintenance cost and proposed the key strategies for improving the sustainable building maintenance budgeting in dealing with the cost overruns. This paper utilizes a qualitative approach through a literature review of secondary data from previous studies. The proposed cost model of maintenance strategies will be used as a basis for further investigation and validation towards promoting the sustainable building maintenance management. The studies identified the push factors that influence the maintenance cost; human factors, tools and equipment, spare parts and materials, funds allocation and available information. Each of the push factors needs to be well-considered to ensure that the maintenance activities can be done efficiently and to avoid the issues of cost overruns.Â Â